Simple Risk Index Score and Hospitalization Mortality in Patients with ST-Elevation Myocardial Infarction - Marfianti, Erlina; Anwar, Sjaiful; Bima Aryatama, Achmad (Green Medical Journal, 2020)
Introduction: Hospitalization mortality in ST-elevation Myocardial Infarction (STEMI) patients areaffected by several factors, including initial identification of the risks at hospital admission. Riskscore tools as a predictor of STEMI complication and death event in STEMI patients is a simple riskindex score. The aim of this study was to determine the association between simple risk index scoreand hospitalization mortality in STEMI patients.Methods: We retrospectively enrolled 60 consecutive patients who were admitted to our hospitaldiagnosed with STEMI. The simple risk index score was calculated for each patient using equation:heart rate x [age/10]2/systolic blood pressure. The patients were assigned into 2 groups according tothis score, high score and low score group. Incidence of death during hospitalization in STEMIpatients was recorded.Results: The total subjects were 60 people. The subjects consisted of 30 patients with low score and30 subjects with high score. The incidence of death during hospitalization in the group of high simplerisk index score were 26 patients, and in the group of low simple risk index score were 13 patients.The association between the simple risk index score and the deaths during hospitalization in STEMIpatients based on statistical analysis was significant (p= 0.00) and value of risk relative (RR) is 2.167;95% CI: 1.368-3.433; (p=0.000).Conclusion: Simple risk index score is associated with hospitalization mortality in ST-elevationmyocardial Infarction (STEMI) patients.